PHYLLANTHUS MYRTIFOLIUS (MOON EX WIGHT) MULL.ARG. AND PHYLLANTHUS TENELLUS ROXB. (PHYLLANTHACEAE) IN JAVA - Muhammad Rifqi Hariri; Arifin Surya Dwipa Irsyam; Afri Irawan; Zakaria Al Anshori; Arieh Mountara; Rina Ratnasih Irwanto (PTTI, 2020)
Phyllanthus myrtifolius (Moon ex Wight) Müll.Arg. and Phyllanthus tenellus Roxb. (Phyllanthaceae) in Java. Floribunda 6(5): 188–194. — Phyllanthus L. is the largest genus in the Phyllanthaceae and consists of 1302 species that are widely distributed in tropical and subtropical regions. There were 20 discovered species of Phyllanthus recorded in the Flora of Java. However, additional species of Phyllanthus in Java can still be discovered in the future. Therefore, this research was aimed to report any additional information on Phyllanthus of Java. Field exploration was conducted in Bandung, Bogor, Jakarta, Sumedang, and Situbondo. Field observation resulted in the findings of two Phyllanthus additional species within the Flora of Java, namely P. myrtifolius (Moon ex Wight) Müll.Arg. and P. tenellus Roxb. P. myrtifolius was widely cultivated as an exotic ornamental plant, while P. tenellus is a newly recorded alien species to Java. The discovery of these species would increase the number of Phyllanthus species in Java.